Pembentukan Empati Siswa Melalui Pengembangan Metode Pembelajaran Aqidah Akhlak di Madrasah Ibtidaiyah - Afifah, Elliya Nafilatul; Astutik, Dwi; Masitoh, Siti; Khoidah, Imro Atul (Social Science Academic, 2024)
Social empathy is an important skill needed in harmonious and respectful social interactions. Improving the quality of character education in Indonesia, especially in instilling empathy values among students, is very important. This study aims to examine and develop an effective Aqidah Akhlak learning method in improving students' social empathy in elementary madrasahs. The library research method was used to collect data from various credible literature sources. The results of the study indicate that conventional learning methods that are less interactive make students less emotionally and cognitively involved, so that the values of Aqidah Akhlak are often only understood as theoretical knowledge. Interactive learning methods such as group guidance, simulations, and role-playing have proven effective in improving students' empathy. This study emphasizes the importance of the role of teachers in implementing appropriate learning methods and the need for cooperation between schools, families, and communities to create a conducive environment for the development of students' social empathy.